Oxygen-Bonding State and Oxygen-Reduction Reaction Mechanism of Pr0.7Ca0.3Mn1−xCoxO3−d (x = 0, 0.1, 0.2, 0.3) - Kanghee Jo; Seungjae Lee; Heesoo Lee (Ceramics, 2023)
We investigated the effects of Co doping on Pr0.7Ca0.3MnO3−d in the perspective of an oxygen-bonding state change. In all compositions, Pr0.7Ca0.3Mn1−xCoxO3−d (PCMCx, x = 0, 0.1, 0.2, 0.3) showed an orthorhombic structure, and the lattice gradually contracted with increasing Co content. The doped Co was mostly present as 2+ and 3+, which decreased the average oxidation value of the B site and created oxygen vacancies for charge compensation. However, as the Co content increased, the proportion of Co3+ increased, and the content of oxygen vacancies gradually decreased. In addition, the ratio of adsorbed oxygen in PCMC0.1 was the highest, and the B-O covalency was enhanced. Accordingly, the electrochemical reaction of oxygen with the cathode material in PCMC0.1 could occur most easily, showing the smallest polarization resistance among the Co-doped Pr0.7Ca0.3MnO3−d. We can confirm the formation of oxygen vacancies via Co doping and the effect of B-O covalency on the oxygen-reduction reaction of Pr0.7Ca0.3MnO3−d.